Visfatin Levels May be an Early Marker of Atherosclerosis in Patients with Acromegaly - Piskinpasa, Hamide; Okuturlar, Yildiz; Dogansen, Sema Ciftci; Akdeniz, Yasemin Sefika; Esen, Ayse; Sadri, Sogol; Pirhan, Osman; Gemici, Aysegul Akdogan; Serin, Sibel Ocak; Gedikbası, Asuman; Adas, Mine; Mert, Meral (Hormone and Metabolic Research, 2019)
The purpose of the study was to compare serum visfatin levels between patients with acromegaly and healthy controls and to evaluate the relationships between visfatin levels and epicardial fat thickness (EFT), carotid intima media thickness (cIMT), and ankle brachial index (ABI). We conducted a cross-sectional case-control study of 54 patients with acromegaly (37 females and 17 males) and 34 healthy controls (22 females and 12 males). Serum visfatin was measured by ELISA. Acromegalic and control participants and those with active or controlled acromegaly were compared with respect to their serum visfatin, clinical and metabolic parameters, EFT, cIMT, and ABI. Linear correlation was used to identify associations between these parameters and visfatin in all participants. Serum visfatin and glycated hemoglobin (HbA1c) were higher in the acromegaly group than in the control group (p<0.001 and p=0.007, respectively). There was no difference in visfatin between the active and controlled acromegaly groups, but HbA1c was higher in the active than the controlled acromegaly group (p<0.04). EFT, cIMT, and ABI were similar between the acromegaly and control groups and between the active and controlled acromegaly groups. Serum visfatin positively correlated with HbA1c, growth hormone (GH), and insulin-like growth factor-1 (IGF-1)/upper limit of normal ratio (r=0.245, p=0.024; r=0.259, p=0.017; and r=0.282, p=0.009, respectively). This study has revealed that a high visfatin level is associated with glycemic dysregulation and higher levels of GH and IGF-1 in acromegalic patients.
Keywords: visfatin; acromegaly; diabetes mellitus; epicardial fat thickness; carotid intima media thickness